Extracción prenatal de calostro una práctica segura para la mujer gestante en su tercer trimestre de embarazo (2022)
Breastfeeding is a fundamental part of parenting, involving new updates in this dynamic can be used as a strategy in favor of avoiding weaning before 6 months of the child's life, which is why prenatal colostrum extraction (PSE) is a practice that promises to be safe from the 37th week of pregnancy when starting a prenatal milk bank. This review of the literature shows the current evidence on the safety of extracting prenatal colostrum and its benefits. We searched and reviewed the literature on current research in prenatal colostrum extraction, of which only 9 articles were included.